Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/s1569-9056(17)31016-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell-based adoptive immunotherapy eradicates and drives differentiation of chemoresistant bladder cancer stem-like cells

Abstract: Background: High-grade non-muscle invasive bladder cancer (NMIBC) has a high risk of recurrence and progression to muscle-invasive forms, which seems to be largely related to the presence of tumorigenic stem-like cell populations that are refractory to conventional therapies. Here, we evaluated the therapeutic potential of Natural Killer (NK) cell-based adoptive immunotherapy against chemoresistant bladder cancer stem-like cells (CSCs) in a pre-clinical relevant model, using NK cells from healthy donors and NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 26 publications
(31 reference statements)
2
29
0
Order By: Relevance
“…A similar preference for CSCs by NK cells was revealed in colon cancer, melanoma, and glioblastoma . In bladder cancer, chemoresistant CSCs treated with activated‐NK cell supernatants demonstrated decreased stemness (as measured by ALDH activity and mRNA panel for stem markers) and increased cisplatin sensitivity . Together, these findings reveal that NK cells can target and kill CSCs if they are able to penetrate the tumor and overcome the tumor's defense mechanisms.…”
Section: Immune Modulationsupporting
confidence: 55%
“…A similar preference for CSCs by NK cells was revealed in colon cancer, melanoma, and glioblastoma . In bladder cancer, chemoresistant CSCs treated with activated‐NK cell supernatants demonstrated decreased stemness (as measured by ALDH activity and mRNA panel for stem markers) and increased cisplatin sensitivity . Together, these findings reveal that NK cells can target and kill CSCs if they are able to penetrate the tumor and overcome the tumor's defense mechanisms.…”
Section: Immune Modulationsupporting
confidence: 55%
“…This combination strategy could be applied clinically as a way to reduce patient relapse rates and improve the utility of both NK-cell transfer and radiotherapy (Figure 1). NK cells have also been future science group Leveraging natural killer cells for cancer immunotherapy Review found to synergize with chemotherapy to target CSCs in preclinical models of nonmuscle invasive bladder cancer [66]. While the role of the cancer stem cell populations in human cancer progression remains controversial, the ability of NK cells to target cancer stem cells may offer a paradigm shift in cancer treatment approaches.…”
Section: Adoptive Nk-cell Therapymentioning
confidence: 99%
“…124 On the other hand, adoptive transfer of NK cells can eliminate the cancer stem cell compartment making the tumour more differentiated and sensitive to chemotherapeutic drugs. 125,126 With regards to innovative therapies, proteasome inhibition, which reduces MHC class I molecules expression, have been shown to upregulate MICA/B and death receptors on several solid tumour CSCs, enhancing NK cell-mediated killing and tumour regression in vivo after NK cell adoptive transfer. 127 Another field of active research is the development of mAbs specifically targeting CSC surface markers.…”
Section: And Solid Tumor Derived Cancer Stem Cellsmentioning
confidence: 99%
“…For instance, radiotherapy, in addition to eliminating tumour bulk, has been shown to induce the upregulation of NK cell‐activating ligands on surviving CSCs, enhancing NK cells cytotoxicity and improving survival when NK cells are infused in the host . On the other hand, adoptive transfer of NK cells can eliminate the cancer stem cell compartment making the tumour more differentiated and sensitive to chemotherapeutic drugs …”
Section: Natural Killer Cells and Solid Tumor Derived Cancer Stem Cellsmentioning
confidence: 99%